ANALYSIS OF GEOMETRIC DIMENSIONING AND TOLERANCING WITH CASE STUDY REQUIREMENT ANALYSIS IN FRANCIS TURBINE ASSEMBLY OF PT ÃâÃâXÃâÃâ FOR ROTORÃâÃâS AXIAL DIRECTION - BOWO ADITIA OKEN (NIM : 23107301); Pembimbing Utama : Dr. Ing. Ir. Indra Djodikusumo, PASKALIS
It is impossible that manufacturing process will produce a product with ideal geometry. So, it is necessary to make geometric tolerance to facilitate the deviation that will occur. So, the assembly of those components will produce the geometric variation in form of gap. These variations will influence assembly process and the performance of final product. Therefore, geometric dimensioning and tolerancing for a product is very important to predict the gap that will occur later in assembly process. Author uses a Francis turbine made by PT “X” as case study. In its assembly process, some components that should be fit are found unfitted. Author does stack tolerance analysis to the components in order to find out whether the design or another factor that causes the problem. Another factor that can cause the problem is manufacturing error, so that it is important to make inspection plan for the components, particularly those that affect the gap. This thesis limits the analysis in axial direction only, meanwhile the analysis in radial direction is explained on thesis with title “Analysis of Geometric Dimensioning and Tolerancing with Case Study Requirement Analysis in Francis Turbine Assembly of PT ”X” for Rotor’s Radial Direction” written by Koko Suherman. So, these two theses actually complete each other. In this thesis compiling, author does literature study, discussion with experts and survey in PT “X” workshop. The results of this thesis are some suggestions for PT “X” to redesign its Francis turbine and inspection proposal to verify products or components after manufacturing process. By these improvements, it is expected that next production of Francis turbine done by PT “X”, will not meet the same problems. Author expects this article can give some idea contributions, knowledge or comparisons for other parties who need some material about geometric dimensioning and tolerancing.